Conductor minimum safe distance analysis: Application of a 20 kV medium voltage airline (SUTM) system - Machmud, Amir; Suranto, Suranto; Hamimi, Hamimi; Harmono, Setyo (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
Medium Voltage Air Line Conductor (SUTM) has a voltage of 20 kV. The SUTM network should have the criteria for electricity safety techniques, including minimum safety distances between the trees and the environment and the effectiveness of electricity distribution development. There are ten stages in the installation of the new SUTM 20 kV network. The results of the study concluded that the Conductor used in the planning of the 20 kV SUTM new network construction was AAACS - 150 mm2. The safe distance between the conductors and the conditions contained Billboards are more than 0.5 meters with a minimum height difference of ± 2.5 meters. Whereas the safe distance between the conductor and the tree is ± 0.5 meters, but the Medium Voltage Network Construction Standard for Electric Power must have a height difference of more than 2.5 meters. The distance between the conductor and billboards is> 0.5 meters, which does not complete the standard instructions.